HAZARD ANALYSIS OF EARTHQUAKE IN THE MAIN CAMPUS OF UNIVERSITAS PENDIDIKAN INDONESIA - Wahyuni, Lies; Rohmat, Dede; Setiawan, Iwan (JURNAL PENDIDIKAN ILMU SOSIAL, 2018)
This study aims at analyzing the hazard level of earthquake in the main campus Universitas Pendidikan Indonesia (UPI) as a means to improve the preparedness in anticipating disasters. The method used was literature study of which data were analyzed using Geographic Information System (GIS). The analysis of the earthquake zones, the potential frequency, and earthquake magnitude, and the distance from the main campus of UPI to the earthquake zone shows that the danger level is high. In terms of zone, the main campus of UPI is located is in the red zone based on the earthquake disaster risk index from the Indonesian National Board for Disaster Management (BNPB) and the earthquake zoning map from the Indonesian Ministry of Public Works. The main campus of Universitas Pendidikan Indonesia which is located in the northern part of Bandung, belongs to the Severe VIII zone meaning that significantly dangerous earthquake resulting in moderate to severe damage possibly occurs. The risk level calculation of the disaster based on its danger, tendency, and capacity is yet to conduct, so that it becomes the suggestion.